1996
DOI: 10.1063/1.531667
|View full text |Cite
|
Sign up to set email alerts
|

Diagrammatic method of integration over the unitary group, with applications to quantum transport in mesoscopic systems

Abstract: A diagrammatic method is presented for averaging over the circular ensemble of random-matrix theory. The method is applied to phase-coherent conduction through a chaotic cavity ͑a ''quantum dot''͒ and through the interface between a normal metal and a superconductor.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
406
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(427 citation statements)
references
References 55 publications
19
406
0
2
Order By: Relevance
“…According to the diagrammatic rules of Ref. 29, the average is then done by connecting all dots by thin lines, summing over all possible ways of pairing up the dots. To leading order in 1/N ch , only planar diagrams contribute, i.e., the diagrams where the thin lines do not cross.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the diagrammatic rules of Ref. 29, the average is then done by connecting all dots by thin lines, summing over all possible ways of pairing up the dots. To leading order in 1/N ch , only planar diagrams contribute, i.e., the diagrams where the thin lines do not cross.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To perform the average over S 0 , we use the diagrammatic technique of Ref. 29 and calculate G to leading order in 1/N ch . First, G is expanded in powers of S F S , G = S F S + S F S S N S F S + S F S S N S F S S N S F S + .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume now that the cavity is separated from the leads by tunnel barriers. Brouwer and Beenakker [101] were able to calculate the distribution function of transmission coefficients in this system for the symmetric case, when the number of channels supported by the left and the right lead are equal, N L = N R = N , and the transmission coefficientsT i in each channel i are same for the left and the right barriers. Assuming in addition NT i ≫ 1 for all channels, they found…”
Section: P(t)mentioning
confidence: 99%
“…However it can be shown that X c depends on the number of open channels, as X c ∼ √ N A general correlation function for QD can be derived in the case of a tunneling probability, Γ, smaller than one (all the above results assume Γ = 1). One finds [14], using the stub model [18],…”
Section: Ericson Fluctuationsmentioning
confidence: 99%